Scientific Approach E-Book on Science Content for VI Grade Elementary School Students - Selvia Arfat; Alexander Hamonangan Simamora; I Komang Sudarma (Universitas Pendidikan Ganesha, 2023)
The use of technology is still lacking in learning, especially in the use of digital-based teaching materials which results in limited teaching materials that can be used by students in learning. This study aims to develop e-books with a scientific approach to science content for Class VI and to analyze the validity and effectiveness of e-books with a scientific approach to science content in Class VI. This research is development research and uses data collection techniques, namely questionnaires, pretest and post-test. Data collection is using questionnaires and tests. Data analysis techniques are using qualitative analysis, quantitative and inferential statistics. The results of this study are the results of validation by learning content experts obtained 95% with very good qualifications, validation results by learning design experts obtained 94.64% with very good qualifications, validation results by learning media experts obtained 95.31% with very good qualifications. The results of the individual trial review obtained 98.33% with very good qualifications, the results of the small group trial review obtained 96.66% with very good qualifications. The results of the effectiveness test of e-books with a scientific approach show significant differences in the results of learning science content before and after using e-book teaching materials. This shows that e-books with a scientific approach are effectively used due to the presentation design of material with a scientific approach, an attractive appearance, and practicality in learning so that they can motivate students in learning science.